KAPASITAS KNOWLEDGE MANAGEMENT UNTUK MENINGKATKAN KERJASAMA DAN INOVASI DALAM PERUSAHAAN (Suatu Tinjauan Teoritis) - Basuki Basuki; Rahmi Widyanti; Mursanto Mursanto (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The purpose of this paper is to study the capacity of Knowledge Management in a theoretical review and aims to understand how companies can strengthen the context of the cooperative elements that exist within the organization to generate innovation. The method used in this paper is the library method based on empirical studies from the results of previous studies and literature studies.The justification of the absorptive capacity typology for innovation efficiency processes has the potential to influence the absorption realized in new products and cause effects on internal research and development in various ways. The impact of joint ventures, supplier cooperation and customer cooperation is significant on absorption.The implication in this paper is to extend the research to other innovation metrics as new organizational methods, new processes, new designs, or new methods of using sales funnels.This paper considers it necessary to analyze the typology of capacities that enable managers to understand the innovation efficiency process in the context of collaboration and make better decisions. Collaboration of collaborative activities, organizational capacity and objectives in internal research and development can obtain higher innovation results.